Implementasi Pasal 249 Undang-Undang Nomor 17 Tahun 2014 dalam Harmonisasi Peraturan Perundang-undangan tentang Sumber Daya Alam oleh Dewan Perwakilan Daerah - Nicolaus Nicolaus; Rasji Rasji (Fakultas Hukum Universitas Tarumanagara, 2020)
There’s overlapping regulation, especially about natural resource in Indonesia. This case lead into disharmony of regulation. It is required an institution that could act on harmonization of regulations about natural resource, that is Council of Regional Representative or called DPD. Through DPD duties and authorities, by case provision of article 249 law number 17 of 2014, there is some of DPD authorities on assisting the execution of regulation harmonization about natural resource. In this research, writers using literature, observation and interview methods to gathering data of implementation article 249 law number 17 of 2014 in regulation harmonization of legislation about natural resource by DPD. Problem that occur is that implementation process of article 249 law number 17 of 2014 was affected upon internal and eksternal factors which cause not optimal DPD performance, specialy on harmonization regulation process. There’s require some effort that could stimulate DPD performance base on article 249, so that process of regulation harmonization about natural resource will work more optimal.